Brain Rot Dalam Perspektif Pendidikan: Tinjauan Sistematis Tentang Paparan Konten Cepat Dan Atensi - Abdul Aziz, Nurdin (Jurnal Syntax Fusion, 2024)
The phenomenon of “brain rot,” or the decline in cognitive capacity caused by exposure to fast-paced content, has become a serious concern in education. With the rise of technology, particularly social media and short-form video applications, students are increasingly exposed to an endless stream of information delivered quickly and relentlessly. This exposure has been linked to a decline in attention span, concentration, and the ability to absorb information in the learning context. This article aims to systematically review the existing literature on the relationship between fast-paced content exposure and attention in educational settings. Based on an analysis of recent studies, this review shows a significant correlation between high consumption of short-form video content and reduced focus and cognitive abilities in students. The findings of this review are expected to provide insights for educators and policymakers in designing effective learning strategies and mitigating the negative impacts of attention-diverting content.